Long-term care based on person-centered care for the older adults in rural Spain: the rural care project - Betegón, Elena; Rodríguez-Medina, Jairo; González-Sanguino, Clara; Irurtia, María Jesús (Frontiers in Public Health, 2025)
Introduction and objectiveThe Rural Care Project is a social and healthcare initiative designed for older adults living in deep-rural areas of the Autonomous Community of Castile and Leon (Spain) who require long-term care (LTC). This intervention program promotes Person-Centered Care (PCC) and active aging to improve quality of life (QoL). The aim of this study is to evaluate the project's effectiveness on QoL by way of a quasi-experimental study.MethodsA total of 416 Spanish participants were divided into three groups: (a) experimental group (N = 102) made up of adults residing in deep-rural areas and receiving targeted home-based support; (b) control: residential care group (N = 170) with people receiving extensive formal care; (c) control: at home (N = 144), consisting of older adults with clinically identified dependency, disability, or chronic illness, who remained in their homes in rural areas and relied mainly on informal support (family, neighbors, or self-management), receiving little or no formal LTC services. The intervention spanned 18–20 months and included social and psychological support, coordination of care services, and periodic assessments by trained professionals. QoL was assessed pre- and post-intervention using the “World Health Organization Quality of Life” (WHOQOL-BREF) scale. Data were analyzed using repeated measures ANOVA, with post hoc tests to explore group differences. Power analysis confirmed adequate sample size to detect medium effects (α = 0.05, power = 0.80, effect size = 0.5).ResultsParticipants reported high satisfaction with personal relationships and housing. The experimental group showed significant improvements in physical and psychological health post-intervention, with moderate and small effect sizes, respectively. Improvements in social relationships and environmental context were limited, appearing mainly in the Control: at home group.Discussion and conclusionThe findings provide evidence that the Rural Care program effectively improves key dimensions of QoL among older adults in deep-rural areas. Recommendations include implementing policy reforms to promote home-based LTC grounded in PCC principles. Prioritizing tailored support to enhance physical health and reduce medical dependency are critical outcomes that should be emphasized. Although the program did not produce significant effects on environmental context and social relationships, observed trends suggest potential benefits if future interventions are expanded to comprehensively address these areas. Thus, future programs should adopt a multifaceted approach, integrating strategies for environmental enhancements and promoting both formal and informal social interactions to empower older adults in decision-making processes.